2023
DOI: 10.1029/2023jg007620
|View full text |Cite
|
Sign up to set email alerts
|

Legacy Phosphorus and Ecosystem Memory Control Future Water Quality in a Eutrophic Lake

P. C. Hanson,
R. Ladwig,
C. Buelo
et al.

Abstract: Lake water clarity, phytoplankton biomass, and hypolimnetic oxygen concentration are metrics of water quality that are highly degraded in eutrophic systems. Eutrophication is linked to legacy nutrients stored in catchment soils and in lake sediments. Long lags in water quality improvement under scenarios of nutrient load reduction to lakes indicate an apparent ecosystem memory tied to the interactions between water biogeochemistry and lake sediment nutrients. To investigate how nutrient legacies and ecosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
(93 reference statements)
0
0
0
Order By: Relevance
“…Kamarainen, Penczykowski, et al (2009) and Kamarainen, Yuan, et al (2009) showed that P supplied by recycling could meet phytoplankton demand for growth, although both internal supply and phytoplankton demand varied from day to day and among locations in Lake Mendota. A model of lake physics and biogeochemistry calibrated to the long-term database for Lake Mendota evaluated the lake's response if the external P load was decreased to zero (Hanson et al, 2023). After elimination of external P load, model results indicated that internal recycling of P would maintain elevated phytoplankton production for nearly a century (Hanson et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamarainen, Penczykowski, et al (2009) and Kamarainen, Yuan, et al (2009) showed that P supplied by recycling could meet phytoplankton demand for growth, although both internal supply and phytoplankton demand varied from day to day and among locations in Lake Mendota. A model of lake physics and biogeochemistry calibrated to the long-term database for Lake Mendota evaluated the lake's response if the external P load was decreased to zero (Hanson et al, 2023). After elimination of external P load, model results indicated that internal recycling of P would maintain elevated phytoplankton production for nearly a century (Hanson et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A model of lake physics and biogeochemistry calibrated to the long-term database for Lake Mendota evaluated the lake's response if the external P load was decreased to zero (Hanson et al, 2023). After elimination of external P load, model results indicated that internal recycling of P would maintain elevated phytoplankton production for nearly a century (Hanson et al, 2023). Despite the low external P loads of 2021, it is plausible that cyanobacteria were sustained by recycling P from sediments and hypolimnetic water entrained across the thermocline.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous long-term monitoring programs exist in smaller lakes which offer a unique opportunity to investigate the conclusions derived here ( Kröger et al, 2023 ; Rhodes et al, 2017 ; Yang et al, 2016 ). Most recently, Lake Mendota (US) has been identified as a long-term water quality model ( Hanson, 2023 ) and was recently used to forecast how legacy phosphorus and ecosystem memory constrain future water quality ( Hanson et al, 2023 ). Moving forward, there is a need to interweave both smaller freshwater systems and the Great Lakes into future paradigm discussions.…”
Section: Conclusion - Caveat Biologus (“Let the Bi...mentioning
confidence: 99%
“…Thus, thermal exchange prior to stratification, in combination with effects of spring air temperature on the phenology of ice thaw and/or stratification onset (Dugan 2021;Ladwig et al 2021;Jane et al 2023), may lead bottom-water conditions to be more correlated with spring, compared to summer, air temperatures (Figure 2a). Here, we refer to this phenomenon as seasonal ecological memory (following, e.g., Ogle et al 2015;Dugan 2021;Hanson et al 2023;.…”
Section: Introductionmentioning
confidence: 99%